Work ability and associated factors among female ready-made garment workers in Bangladesh - Fathema Tuz Zohra; Md. Abdullah Saeed Khan; Shahria Sattar (PLoS ONE, 2025)
Background The ready-made garment industry plays a crucial role in Bangladesh’s economy and has made a significant contribution to womenempowerment by employing millions of female workers. The work ability, reflecting the productivity and well-being of a worker, has been less explored among female garment workers. This study aimed to explore this gap. Methods This cross-sectional study was conducted among 395 female garment workers aged ≥18 years at a factory in Dhaka from August-December 2023. Work ability was assessed using the Work Ability Index (WAI). Sociodemographic and work-related factors associated with WAI scores were identified using linear regression analysis. Results The average age (±SD) of the participants was 31.05 ± 6.71 years. The Work Ability Index scores among participants showed a good mean (±SD) score of 40.65 ± 2.71 [Range: 7–49]. Younger age (p < 0.001), not having any children (p = 0.012), lower family income (<12,000 BDT) (p < 0.001), higher duration of job (p = 0.016) and working in the finishing section (p = 0.001) were associated with higher WAI scores. After adjustment, age (β = −0.06, 95% CI −0.10 to −0.01), income (β = −0.63, 95% CI −1.20 to −0.05), and working in finishing (adjusted β = 1.77, 95% CI: 0.32 to 3.21 compared to administration section) were independently associated with WAI scores. Conclusions The study identified several factors that can be considered when planning interventions to enhance work ability and well-being of female garment workers.